The role of a company's internal control system in fraud prevention - Dragomir Dimitrijevic; Vesna Milovanovic; Vladimir Stancic (e-Finanse: Financial Internet Quarterly, 2015)
The emergence of internal control over specific segments of activities has been associated with management needs for evaluation of the consistency between the actual situation and development targets. Monitoring activities should enable detection and timely reaction to possible target-related deviations. While responding to complex market needs, companies are exposed to numerous internal and external influences, some of which may cause significant damage. Companies have realized that it is safer and cheaper to establish their own internal control systems in order to prevent such influences. The aim of this work is to show how the overall quality of control and The emergence of internal control over specific segments of activities has been associated with management needs for evaluation of the consistency between the actual situation and development targets. Monitoring activities should enable detection and timely reaction to possible target-related deviations. While responding to complex market needs, companies are exposed to numerous internal and external influences, some of which may cause significant damage. Companies have realized that it is safer and cheaper to establish their own internal control systems in order to prevent such influences. The aim of this work is to show how the overall quality of control and company performance is improved through implementation of preventive methods by internal controls, and to indicate that a developed system of internal control represents a protective barrier against various kinds of data manipulation and fraud inside the companies. Special attention was paid to fraud in financial statements since it can cause the most serious damage leading to instability of the economic-financial environment.
Keywords: K4; G1; G28; 330; internal control; fraud prevention; financial statements; management